Perceived parental acceptance/rejection, some family characteristics and conduct disorder in adolescents - Kostić, Jelena; Nešić, Milkica; Stanković, Miodrag; Žikić, Olivera (Vojnosanitetski pregled, 2014)
Background/Aim. Conduct disorder is characterized by repetitive and persistent presence of dissocial, aggressive and defiant behavioral patterns, thus represents important public issue with comprehensive and far-reaching consequences both for the individual and society. The aim of this study was to investigate the differences in sociodemographic family characteristics and the prominence of parental acceptance/rejection dimensions in groups of adolescents with and without conduct disorder, as well as to examine the connection between parental acceptance/rejection dimensions and externalizing symptoms in the group of adolescents with conduct disorder. Methods. This research was conducted on 134 adolescents, aged 15 to 18, using the Parental Acceptance/Rejection Questionnaire (PARQ child), Youth Self-Report (YSR), and a questionnaire constructed for the purpose of this survey. Results. The results showed that the number of adolescents with conduct disorder coming from divorced families was significantly higher than from complete families (44.8% vs 13.4%, respectively; p
Keywords: conduct disorder; adolescent; family; risk factors; socioeconomic factors; questionnaires